2010
DOI: 10.1007/s11125-010-9169-z
|View full text |Cite
|
Sign up to set email alerts
|

Family, community, and educational outcomes in South Asia

Abstract: In this article, we review research on the economics and sociology of education to assess the relationships between family and community variables and children's educational outcomes in South Asia. At the family level, we examine the variables of family socioeconomic status (SES), parental education, family structure, and religion and caste. At the community level, we assess the limited research on the relationships between economic, cultural, and social characteristics and children's educational outcomes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The gender gap in educational outcomes is largely driven by community and family attitudes towards girls’ education in the south Asian context ( Sonalde et al 2010 ). For instance, studies have shown that the importance of the social and religious roles attributed to sons in the Indian kinship system, the huge financial burden at the time of a girl’s marriage, and the perception that the returns to a daughter’s education mainly benefit her in-laws’ family are among the prominent factors affecting the allocation of higher levels of emotional and financial resources to sons at the expense of daughters ( Chudgar et al, 2005 , Chudgar and Shafiq, 2010 ). Also, as suggested previously, the cohort of women analyzed in the present study may have experienced even worse forms of discrimination during their early childhood and adulthood, as they were born and brought up in an environment of even greater cultural rigidity than under present day conditions ( Oksuzyan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The gender gap in educational outcomes is largely driven by community and family attitudes towards girls’ education in the south Asian context ( Sonalde et al 2010 ). For instance, studies have shown that the importance of the social and religious roles attributed to sons in the Indian kinship system, the huge financial burden at the time of a girl’s marriage, and the perception that the returns to a daughter’s education mainly benefit her in-laws’ family are among the prominent factors affecting the allocation of higher levels of emotional and financial resources to sons at the expense of daughters ( Chudgar et al, 2005 , Chudgar and Shafiq, 2010 ). Also, as suggested previously, the cohort of women analyzed in the present study may have experienced even worse forms of discrimination during their early childhood and adulthood, as they were born and brought up in an environment of even greater cultural rigidity than under present day conditions ( Oksuzyan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have used education production function model to understand how factors like budget, and school resources affect students' educational outcomes e.g. school attainment, enrolment, and learning (Chudgar and Shafiq, 2010;Hanushek, Link and Woessmann, 2011;Jimenez and Sawada, 2003;di Gropello and Marshall, 2005).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Many scholars find the effects of households' socioeconomic background, namely, parental education, occupational prestige, and other indicators of home circumstances, on children's academic performance larger than the effects of school and teacher quality (Coleman et al, 1966;Chudgar and Shafiq, 2010). Other scholars claim that school factors such as quality of facilities, quality of teachers, and type of schools significantly determine the level of students' outcomes particularly in the context of developing countries (Heyneman and Loxley, 1983;Jimenez et al, 1991).…”
Section: Studies On Determining Factors Of Educational Attainmentmentioning
confidence: 99%